2016
DOI: 10.1371/journal.pntd.0005262
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antibodies to Zika Virus in Mothers from Hawaii Who Delivered Babies with and without Microcephaly between 2009-2012

Abstract: Zika virus (ZIKV) is an emerging mosquito-borne pathogen. ZIKV infection is linked to the development of severe fetal abnormalities that include spontaneous abortion, stillbirth, hydranencephaly, and microcephaly. ZIKV outbreaks have been recorded in the United States. We recently demonstrated the first congenital ZIKV infection in the United States. In this study, we investigated archived blood samples from six mothers who gave birth to babies with microcephaly and 12 mothers who gave birth to healthy babies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(55 citation statements)
references
References 15 publications
0
54
0
Order By: Relevance
“…A recent retrospective study of six infants with microcephaly born in Hawaii found an association between maternal ZIKV infection and infant microcephaly as early as 2009, although further phenotypic description of these infants with possible CZS was not provided (M. Kumar et al, ). This raises the question that if CZS existed prior to the 2013 French Polynesia outbreak, why was it not recognized earlier?…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective study of six infants with microcephaly born in Hawaii found an association between maternal ZIKV infection and infant microcephaly as early as 2009, although further phenotypic description of these infants with possible CZS was not provided (M. Kumar et al, ). This raises the question that if CZS existed prior to the 2013 French Polynesia outbreak, why was it not recognized earlier?…”
Section: Discussionmentioning
confidence: 99%
“…From those, 138 studies were ruled out based on the exclusion criteria. After the full-text review, a total of 12 observational studies were included in the synthesis of the literature [29][30][31][32][33][34][35][36][37][38][39][40] (Figure 1). Of the 12 eligible studies, six authors provided the primary data [29,34,[37][38][39][40], and therefore were included in the meta-analysis.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The twelve included studies were published between 2015 and 2018; ten of them had Research Ethics Board approval and two declared themselves exempt from this approval [30,39]. Five were cohort studies [30,[33][34][35][36], three were case-controls studies [31,32,38], three were case-series [29,37,39], and one was a cross-sectional study [40]. The studies de ned as case-series [29,37,39] were conducted based on surveillance data -local surveillance system and hospital-based surveillance -and reported only ZIKV infected cases with varied outcomes.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations